Меры по предотвращению экологических коррупционных преступлений (Measures to Prevent Environmental Corruption Crimes) - Elvira, Ade Irma; Nasution, Latipah (Jurnal Cita Hukum, 2019)
AbstractThe international conference on the environment which was held in Stockholm, Sweden in 1972 to Rio de Janeiro 1992, to Rio + 10 in Johannesburg 2002, emphasized the need for coordination and integration between natural resources, human resources, and artificial resources in every national development, with a population, development approach, and the environment to the integration of social, economic and environmental aspects. The Government of Indonesia is committed to carrying out sustainable development with various efforts, one of which is the issuance of environmental permits. The environmental damage that occurs in the region, is the responsibility of local governments as a whole from the existence of the authority to issue permits granted. Corruption in the environmental sector is a barrier to the path of sustainable development. Licensing is one of the instruments to prevent natural damage as well as controlling environmental management activities. But on the other hand, licensing is a fertile ground for corrupt practices that hinder sustainable development. The purpose of this study is to provide an understanding of the importance of supervision of licensing for the creation of the concept of environmentally sustainable development. The research method used is a normative juridical research method that is descriptive analysis through doctrinal law review. It can be concluded that environmental problems and obstacles that occur in the licensing sector are often mixed with corrupt practices by the government which has the authority to give permits. This has caused delays in sustainable development and damage to the environment which has an impact on the community's economic sector.Keywords: Natural Resources (SDA), Licensing, Local Government Authority, Corruption Abstrak Konverensi internasional tentang lingkungan yang dilaksanakan di Stockholm, Swedia pada 1972 menuju Rio de Janeiro 1992, sampai dengan Rio + 10 di Johanesburg 2002, menekankan perlu adanya koordinasi dan integrasi antara SDA, SDM, dan sumberdaya buatan dalam setiap pembangunan nasional, dengan pendekatan kependudukan, pembangunan, dan lingkungan sampai dengan integrasi aspek sosial, ekonomi, dan lingkungan. Pemerintah Indonesia berkomitmen melaksanakan pembangunan berkelanjutan dengan berbagai upaya, salah satunya dalam penerbitan izin lingkungan. Kerusakan lingkungan yang terjadi di daerah, merupakan tanggung jawab pemerintah daerah sebagai satu kesatuan dari adanya kewenangan mengeluarkan perizinan yang diberikan. Korupsi yang terjadi di sektor lingkungan merupakan penghalang jalannya pembangunan berkelanjutan. Perizinan merupakan salah satu instrumen pencegah kerusakan alam sekaligus sebagai pengendali aktifitas pengelolaan lingkungan hidup. Namun disisi lain, perizinan menjadi ladang subur terjadinya praktik korupsi yang menghambat pembangunan berkelanjutan. Tujuan penelitian ini untuk memberikan pemahaman terkait pentingnya pengawasan terhadap perizinan demi terciptanya konsep pembangunan berkelanjutan berwawasan lingkungan. Metode penelitian yang digunakan yaitu metode penelitian yuridis normatif yang bersifat deskriptif analisis melalui pengkajian hukum doctrinal.Dapat disimpulkan bahwa permasalahan lingkungan hidup dan hambatan yang terjadi ada pada sektor perizinan seringkali dicampuri dengan praktik korupsi oleh pemerintah yang berwenang memberikan izin. Hal ini menimbulkan terhambatnya pembangunan berkelanjutan serta kerusakan pada lingkungan yang berdampak pada sektor perekonomi masyarakat.Kata kunci: Sumber Daya Alam (SDA), Perizinan, Kewenangan Pemerintah Daerah, Korupsi АннотацияМеждународная конференция по проблемам окружающей среды состоялась В Стокгольме, Швеция в 1972 году. По результатам этой конференции Индонезия взяла на себя обязательство осуществлять устойчивое развитие, и по сей день предпринимает различные усилия для поддержания этой договоренности. Коррупция в области охраны окружающей среды и природных ресурсов является препятствием на пути устойчивого развития. Лицензирование является одним из инструментов предотвращения разрушения природы, а также контроля за деятельностью по управлению окружающей средой. С другой стороны, лицензирование также становится благодатной почвой для коррупции. Местные органы власти в этом случае имеют право выдавать разрешения на деятельность, которая может нанести экологический ущерб в данной местности. Целью данного исследования является оценка деятельности в области лицензирования в экологической сфере и перспектив устойчивого экологического развития в Индонезии. Основным методом исследования была оценка нормативно-правовых актов в сфере экологического регулирования. На основании описательного анализа можно сделать вывод, что препятствия, возникающие на уровне отраслевого лицензирования, часто решаются методами коррупции со стороны государственных органов, что препятствует устойчивому развитию экологической сферы, наносит ущерб окружающей среде и препятствует развитию экономики.Ключевые слова: природные ресурсы (ПДД), лицензирование, Местные органы власти, коррупция